(untitled) (International Seven Journal of Multidisciplinary, 2023)
The family institution has undergone significant transformations throughout history, adapting to the values and beliefs of different eras and social groups. This study focused on the analysis of the "Namoro Contract," an agreement established between two individuals involved in a romantic relationship with the purpose of preventing the relationship from being legally considered a Common-Law Marriage. This contract is formalized through registration at a notary public, with its main objective being the resolution of patrimonial issues. In addition to addressing patrimonial implications, this work delved into the definition of dating and its distinctions concerning Common-Law Marriage, exploring the essential elements present in such contractual agreements. The study also emphasized the importance of understanding the nuances that differentiate these relationship modalities, considering both legal and social aspects. In summary, this study not only delved into the analysis of the Namoro Contract and its patrimonial implications but also sought to contextualize these practices within the broader panorama of transformations in the family institution, taking into account both legal and social perspectives.